One‐year real‐world outcomes of bevacizumab for the treatment of macular oedema secondary to retinal vein occlusion. (4th August 2022) - Wang, Nancy; Hunt, Adrian; Nguyen, Vuong; Shah, Janika; Fraser‐Bell, Samantha; McAllister, Ian; Barthelmes, Daniel; Gillies, Mark; Squirrell, David
Abstract: Background: Bevacizumab is the only agent that many people can afford, yet there are only limited data on whether it improves macular oedema (MO) secondary to retinal vein occlusion (RVO) in real‐world clinical practice. Here we studied 12‐month real‐world treatment outcomes of bevacizumab for RVO‐related MO. Methods: This was a multicentre, observational study analysing 12‐month data from the Fight Retinal Blindness! (FRB) database. We studied treatment‐naïve eyes with MO secondary to RVO commencing bevacizumab therapy between June 2009 and June 2019. Visual acuity (VA) and central subfield thickness (CST) were measured at baseline, 6 and 12 months. The primary outcome was a change in VA from baseline to 12 months. Results: Two hundred and twenty treatment naive eyes were analyzed. The baseline VA for BRVO was better than CRVO (55.8 vs. 42.6 LogMAR letters) and this gap widened over the 12‐month period, with a 12‐month VA change of +14.0 (95% CI 11.1, 16.8) letters for BRVO and + 11.9 (95% CI 6.4, 17.4) for CRVO. The mean CST at baseline was 511 μm for BRVO and 627 μm for CRVO, falling at 12 months by −155 μm (−190, −121) in BRVO and −198 μm (−252, −145) in CRVO. The median number of injections for BRVO and CRVO completers was 7 (5, 9). Conclusions: Bevacizumab can be an effective treatment of RVO‐MO in a real‐world setting with outcomes approaching those reported by the seminal clinical trials. The functional and anatomical outcomes of intravitreal therapy were better for BRVO than CRVO.